Transduction of miRNA-155 and miRNA-34a in Oral Squamous Cell Carcinoma Cell Line - Abd El Rahman M. Sharfeldeen; Zeinab M. Abulwafa; Ibraheem K. Bamaga; Mohamed A. Mohamed; Hoda A. Fansa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Objective: to assess the impact of miRNA-155 and miRNA-34a suppression and replacement on the possibility of human Tongue squamous cell carcinoma (SCC) cell line (HNO97).Design: In vitro study.Setting: Global Research Labs, Medical Center2, Nasr City, Cairo, EgyptInterventions: The HNO97 cells were transfected with miR-155 and miR-34a imitates and inhibitors, then the cell capability was assessed using the MTT assay, and the c-Myc and CDK6 genes expression was calculated in treated and untreated cells using SYBER green based quantitative polymerase chain reaction.Main outcome measure: To detect how transduction of oral SCC (OSCC) cell line with miRNA-155 and miRNA-34a mimic and inhibitor affects the expression of c-Myc and CDK6 genes.Results: The cell viability was precisely as well as directly linked with the expression of miR-155 and the case was the opposite when miRNA-34a was used, in addition, higher expression level of c-Myc gene was combined with miR-155 mimic and miR-34a suppression and, the CDK6 gene expression showed an increase in cells treated with miR-155 mimic as well as miR-34a mimic and inhibitor.Conclusions: miR-155 has a significant oncogenic effect on OSCC cell lines by increasing the c-Myc and CDK6 gene expression, but miR-34a lacks that well defined effect.